Monitoring blood biomarkers to predict nivolumab effectiveness in NSCLC patients. (April 2019) - Passiglia, Francesco; Galvano, Antonio; Castiglia, Marta; Incorvaia, Lorena; Calò, Valentina; Listì, Angela; Mazzarisi, Salvatore; Perez, Alessandro; Gallina, Giuseppe; Rizzo, Sergio; Soto Parra, Hector; Bazan, Viviana; et al.
Background: We investigated whether early dynamic changes of circulating free (cfDNA) levels as well as the neutrophil to lymphocyte ratio (NLR) could predict nivolumab effectiveness in pretreated patients with advanced non-small cell lung cancer (NSCLC). Methods: A total of 45 patients receiving nivolumab 3 mg/kg every 2 weeks were enrolled. Patients underwent a computed tomography scan and responses were evaluated by the response evaluation criteria in solid tumors. Peripheral blood samples were obtained from the patients and the cfDNA level as well as the NLR were assessed. Time to progression (TTP) and overall survival (OS) were determined. Results: Patients with increased cfDNA >20% at the sixth week reported significantly worse survival outcomes (median OS: 5.7 versus 14.2 months, p < 0.001; median TTP: 3.3 versus 10.2 months, p < 0.001), as well as patients with increased NLR >20% (median OS: 8.7 versus 14.6 months, p = 0.035; median TTP: 5.2 versus 10.3 months, p = 0.039). The combined increase of cfDNA and NLR >20% was associated with significantly worse survival outcomes as compared with the remained population (median OS: 5.8 versus 15.5 months, p = 0.012; median TTP: 3.2 versus 11.9 months, p = 0.028). Multivariable analysis identified three significant factors associated with worse OS: combined cfDNA/NLR increase >20% [hazard ratio (HR): 5.16; 95% confidence interval (CI), 1.09–24.29; p = 0.038], liver metastasis (HR: 0.44; 95% CI, 0.20–0.96; p = 0.038), and extra-thoracic disease (HR: 0.33; 95% CI, 0.12–0.89; p = 0.029). Conclusion: An early combined increase of both cfDNA and NLR over the course of the first 6 weeks of nivolumab therapy predicted worse survival in pretreated patients with advanced NSCLC, suggesting a potential role in the real-time monitoring of immunotherapy resistance.